Influencing Factors of Knowledge, Attitude, and Practice regarding Medical Nutrition Therapy in Patients with Diabetes: A National Cross-Sectional Study in Urban China - Zijian Li; Haimin Jin; Wei Chen; Zilin Sun; Lulu Jing; Xiaohui Zhao; Sainan Zhu; Xiaohui Guo; China NEEDs Study Group (Journal of Diabetes Research)
To investigate the knowledge-attitude-practice (KAP) score in diabetes patients living in urban China regarding Medical Nutrition Therapy (MNT) and explore the influencing factors, this national survey recruited diabetes and prediabetes patients in 40 hospitals across 26 provinces in China. A self-designed questionnaire was used to collect the data and assess the knowledge, attitude, and practice regarding MNT. Logistic regression was used to explore the factor influencing KAP scores. A total of 6441 diabetes patients (mean age: 60.02±13.14 years) completed this survey. The mean glycosylated hemoglobin (HbA1c) level was 8.12±2.12%, and the control rate of HbA1c (HbA1c < 7.0%) was 38.92%. Of the total, 53.56% had received MNT education. Over half of the patients had a poor total KAP score as well as poor K, A, and P scores. Patients with higher KAP scores had higher control rate of HbA1c (P<0.05) but lower levels of fasting plasma glucose (FPG) and 2-hour postprandial blood glucose (2h-PG). Gender, occupation, residence, education level, and MNT education could influence the KAP scores (P<0.05). This study showed that diabetes patients in urban China generally had poor understandings and practices related to MNT. Patients with higher KAP scores exhibited better control of blood glucose.